Pengaruh Model Pembelajaran Aktif Berbasis Inkuiri (ABI) Terhadap Kemampuan Berpikir Kritis Siswa - Indah Dharmawati; Saiful Prayogi; Samsun Hidayat (Lensa: Jurnal Kependidikan Fisika, 2018)
[Title: The Effect of Inquiry-Based Active Learning (ABI) on Students' Critical Thinking Ability]. The critical thinking ability is the ability to learn and analyze information through skills: interpretation, analysis, evaluation, inference, explanation and self-regulation. Inquiry-based active learning model (ABI) is a learning model that accumulates active and inquiry learning which aims to develop students critical thinking ability through phases: 1) introduction and establishing sets; 2) presenting cognitive conflicts; 3) submitting the hypothesis; 4) collecting data (experiment) for hypothesis testing; 5) formulate explanations and/or conclusions; 6) reflection. This research aims to determine the effect of inquiry-based active learning model (ABI) on students’ critical thinking ability. This research is quantitative research (quasi-experiments), this experimental research uses pretest-posttest control group design. This research is used cluster random sampling. The sample in this research amounted to 37 students as experimental class and 34 students as control class. The inferential analysis is used to test the influence of inquiry-based active learning model (ABI) in a review of improvement of students’ critical thinking ability. Hypothesis test results also show t-test value lower than t-table value, so it can be stated that the Inquiry-Based Aktive Learning Model (ABI) has a positive effect on critical thinking ability of X-GEO at SMKN 3 Mataram school year 2017/2018.